Cooperative NOMA with Antenna Selection Schemes - Aldababsa, Mahmoud; Kucur, Oğuz (IEEE, 2019)
In this paper, we study the performance of non-orthogonal multiple access (NOMA) based on antenna selection schemes in dual hop amplify-and-forward relay network over Rayleigh fading channels. In the network, base station and mobile users are equipped with multiple antennas, whereas the relay has multiple receive antennas and single transmit antenna. For signal transmission and reception, joint transmit and receive antenna selection and receive antenna selection are applied in the first and second hops, respectively. We investigate the outage behavior of the system by driving exact closed-form expression for outage probability (OP). Next, asymptotic OP is obtained, from which the diversity order can be easily achieved. Then, we study the ergodic sum rate of the system, and explicit expressions for the lower and upper bounds of the ergodic sum rate are found. Analytical results are verified by Monte Carlo simulations.
27th Signal Processing and Communications Applications Conference (SIU) -- APR 24-26, 2019 -- Sivas Cumhuriyet Univ, Sivas, TURKEY
Keywords: Non-orthogonal multiple access; Joint transmit and receive antenna selection; Receive antenna selection